Indomethacin Prevents Neuronal Apoptosis in Newborn Rats with Hypoxic-Ischemic Brain Injury - Taskin, Erdal; Satar, Mehmet; Zorludemir, Suzan; Ozcan, Kenan (Ortadogu Ad Pres & Publ Co, 2011)
Objective: Cyclooxygenase pathway and prostaglandins play an important role in the pathogenesis and delayed mechanisms of hypoxic-ischemic brain injury. The aim of this study was to investigate the effect of different doses of indomethacin, a nonselective cyclooxygenase inhibitor, on neuronal apoptosis in rats with hypoxic-ischemic brain injury. Material and Methods: Seven-day-old rat pups with the Rice model of hypoxic-ischemic cerebral injury were randomly divided into five groups. Group 1 (n=15) pups were given physiologic saline, neither ligation nor hypoxia were performed. Group 2 (n=15) pups were treated with physiologic saline after hypoxic-ischemia. Group 3 (n=15) pups were treated with indomethacin at a dose of 2 mg/kg before hypoxic ischemia. Group 4 (n=15) pups were treated with three doses of indomethacin at a dose of 2 mg/kg every 12 h after hypoxic-ischemia. Group 5 (n=15) pups were treated with three doses of indomethacin, at a dose of 4mg/kg every 12 h after hypoxic ischemia. After 72 hours, the rats were decapitated and brain hemispheres were evaluated by the TUNEL (Terminal deoxynucleotidyl transferase mediated dUTP nick end labeling) staining method. Results: Indomethacin treatment, either before or after hypoxia, resulted in a significant reduction in the numbers of apoptotic cells in the rat brain when compared to those who were treated with physiologic saline after hypoxic-ischemia (P<0.001). Conclusion: Our results demonstrated that indomethacin administration, either before or after hypoxic-ischemia, reduces neuronal apoptosis; and we propose that indomethacin may be a potential choice of treatment for hypoxic-ischemic brain injury.
İndometazin hipoksik-İskemik beyin hasarlı yenido?an ratlardaki nöronal apopitozisi önler
Keywords: Hypoxia-ischemia, brain; apoptosis; indomethacin